Rohana Kuddus: Gender Dan Gerakan Sosial-Politik - Soraya Oktarina (Journal of Feminism and Gender Studies, 2021)
Emancipation and Gender Equality became a hot issue in the 20s. Women are judged to be entitled to the same rights as men in education, politics, economics, and others. Rohanna Kuddus, a woman from Koto Gadang, West Sumatra, dedicates her life to improving women of origin. In the 19th century, Minangkabau women were still underprivileged and marginalized. Rohana Kuddus believes that women must make a move to change their condition. Various movements were pioneered by Rohanna Kudus, ranging from gender struggle movements to politics. Rohana Kuddus: Gender and Socio-Political Movements uses research methods to collect interview sources, books, journals, and data from the internet that discusses Ruhana Kuddus. The limit of this paper is to look at the movements of Rohanna Kuddus in achieving gender equality and the various political movements that are running.